2016
DOI: 10.18632/oncotarget.8971
|View full text |Cite
|
Sign up to set email alerts
|

Validation of DAB2IP methylation and its relative significance in predicting outcome in renal cell carcinoma

Abstract: We have recently reported tumor suppressive role of DAB2IP in RCC development. In this study, We identified one CpG methylation biomarker (DAB2IP CpG1) located UTSS of DAB2IP that was associated with poor overall survival in a cohort of 318 ccRCC patients from the Cancer Genome Atlas (TCGA). We further validated the prognostic accuracy of DAB2IP CpG methylation by pyrosequencing quantitative methylation assay in 224 ccRCC patients from multiple Chinese centers (MCHC set), and 239 patients from University of Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
(32 reference statements)
0
23
0
Order By: Relevance
“…Each year, approximate 270,000 cases will be diagnosed as having renal cancer around the world 16-18. At present, considering the use of advanced instruments and innovative therapy, some cases of ccRCC can be diagnosed at early stages and cured by surgical resection and chemo-radiotherapy 5.…”
Section: Discussionmentioning
confidence: 99%
“…Each year, approximate 270,000 cases will be diagnosed as having renal cancer around the world 16-18. At present, considering the use of advanced instruments and innovative therapy, some cases of ccRCC can be diagnosed at early stages and cured by surgical resection and chemo-radiotherapy 5.…”
Section: Discussionmentioning
confidence: 99%
“…Such a rich collection of data gathered from a large number of patients have a great potential to be used in robust statistical analyses, thereby enabling improved survival prediction. Therefore, several studies [35,36,43,[47][48][49][50] rely on TCGA as a complementary resource for biomarker assessment. We believe that MethSurv will be a promising tool for similar studies to explore methylation-based biomarkers and to perform in silico validation as illustrated in the case studies section.…”
mentioning
confidence: 99%
“…In addition, we performed Kaplan-Meier analysis to evaluate the association of methylated CLDN11 with overall survival. We used the mean methylation level of tumor tissues to classify patients into two groups: 30 patients were placed into the hypermethylation group, and the remaining patients were categorized as the hypomethylation group [ 29 ]. Kaplan-Meier analysis indicated that patients with higher methylation frequency tended to have a poorer overall survival compared to patients with lower methylation (log-rank test, p =0.007, Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%